ON THE METHODOLOGICAL PROBLEMS OF IMPROVING THE PUBLIC IMAGE (Eureka Journal of Humanities and Social Research, 2026)
The article examines theoretical approaches to understanding the image of a state in international relations, its functions, structure, and main components. Special attention is given to the technology of image formation based on social and psychological principles, as well as its significance in the context of globalization and informatization. The author analyzes the role of image as a tool for achieving strategic goals, protecting national interests, and strengthening international cooperation, emphasizing its importance for realizing a state's potential on the global stage.
Keywords: Image, strategic goals, national interests, cooperation.